(3GdeGFIs - (3YjSi Hf jMji GdeSjMj GdLQLGfj, CHh Sgd , J (B401 (3g` s ((3eOjfI GdSdGe s)
(3ChdgG (B:s
(3bGd CHh Sgd (B:(3gPG gh GdcJGH GdChd ef cJHfG ai UfGYI GdWH , hbUOfG ajg Cf fJcde ajeG jLH JbOjeg s
(3BNQgG (B:s
(3hPdc EPG CNP ef GdeGA YfO Pdc HGddHf heGA GdTYjQ hOb GdHfaSL s
(3QJHg Ydi eGFI ebGdI bUjQI ai ehVhYGJ GdWHs
(3hSeGgG cJHkGs
(3YOOgG ai GdcJGH GdChd GdPi SeGg (B: (3GdeONd Edi GdUfGYI GdWHjIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdWHs